Technical Support and Capacity Building for Mali-Météo in Data Sharing Tool (DST) and Enhancing National Climate Services initiative (ENACTS) - Dinh, Dannie; Dinku, Tufa; Faniriantsoa, Rija (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents the technical assistance and capacity building provided by the International Research Institute for Climate and Society (IRI) at Columbia University to Mali’s National Meteorological Agency (Mali-Météo) for the deployment and operationalization of the Data Sharing Tool (DST) and the Enhancing National Climate Services (ENACTS) tools. Recognizing the challenges of limited meteorological data in sub-Saharan Africa, ENACTS aims to improve data quality by integrating ground-based and satellite observations to produce spatially complete climate datasets. To enhance the usability and dissemination of these datasets, IRI developed a DST tailored to Mali Météo needs, enabling secure and selective data sharing with trusted partners. This report outlines the steps taken to install and test the DST, the capacity-building activities conducted—including the training of six Mali-Météo staff (two women)—and the core features of the DST that support user-specific data access. The report also details planned next steps, including enabling external access to the DST via a public IP and updating the system with the most recent ENACTS datasets. This initiative significantly strengthens Mali-Météo capacity to deliver user-responsive climate services and contributes to the broader objective of enhancing climate-informed decision-making in Mali’s agricultural and environmental sectors.